1981
DOI: 10.3758/bf03202349
|View full text |Cite
|
Sign up to set email alerts
|

Memory for actions in scripted activities as a function of typicality, retention interval, and retrieval task

Abstract: This study examined memory for information that varies in typicality (relevance) to a central organizingschema. Subjects listened to scripted activities and were given recall and recognition tests after different retention intervals. Data supported a schema-pointer-plus-tag model that specifies how memory for scripted actions varies as a function of typicality, retention interval, and retrieval task. Several mathematical formulations of the model were tested in order to simulate the recall and recognition data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
4
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(105 citation statements)
references
References 15 publications
6
93
4
2
Order By: Relevance
“…The typicality effect in recognition memory, by contrast, should not depend on the length of the retention interval because recognition memory is generally less reconstructive than recall memory. In accordance with these predictions, Smith and Graesser (1981) found an atypicality advantage in recognition memory for all retention intervals, whereas the atypicality advantage in recall memory was limited to short retention intervals and reversed into a typicality advantage approximately 48 h after testing. Recently, however, Davidson (1994) demonstrated that the reversal of the typicality effect in recall memory is limited to atypical items describing relatively pallid and routine actions.…”
Section: Discussionsupporting
confidence: 67%
“…The typicality effect in recognition memory, by contrast, should not depend on the length of the retention interval because recognition memory is generally less reconstructive than recall memory. In accordance with these predictions, Smith and Graesser (1981) found an atypicality advantage in recognition memory for all retention intervals, whereas the atypicality advantage in recall memory was limited to short retention intervals and reversed into a typicality advantage approximately 48 h after testing. Recently, however, Davidson (1994) demonstrated that the reversal of the typicality effect in recall memory is limited to atypical items describing relatively pallid and routine actions.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, consistent with prior research on other schemata (e.g., Kleider, Pezdek, et al, 2008;Lampinen et al, 2001;Smith & Graesser, 1981), the life script schema played a more substantial role in shaping memory as the length of the retention interval increased. Second, though our findings in support of Hypothesis #3, regarding remember/know judgements for correctly recognized events, were less strong, we did find a trend for schema-inconsistent events to be given remember judgements more frequently than schema-consistent events.…”
Section: High-frequency Versus Low-frequency Eventssupporting
confidence: 84%
“…for the behavior of instructors in a classroom (Neuschatz, Lampinen, Preston, Hawkins, & Toglia, 2002); for common scenes such as taking one's dog to the veterinarian or going to the beach (Bower, Black, & Turner, 1979;Graesser, Gordon, & Sawyer, 1979; Graesser, Woll, Kowalski, & Smith, 1980;Lampinen, Faries, Neuschatz, & Toglia, 2000;Shapiro & Fox, 2002;Smith & Graesser, 1981); for stereotypes about categories of people (e.g., gender stereotypes;…”
Section: Shapes Memory For Fictional Life Storiesmentioning
confidence: 99%
“…Another possibility is that these musical ornaments are easily remembered because they are salient or relatively atypical contour patterns (e.g., D. A. Smith & Graesser, 1981) that stand out from the surrounding musical context. This hypothesis is supported by the fact that the experimental corpus included a relatively small proportion of notes that completed alternation (12.1%) and pair patterns (2.4%).…”
Section: What Are the Fundamental Units For Melody Identification?mentioning
confidence: 99%